Resilience is associated with coping with musculoskeletal pain in nursing professionals - Schulz, Carmen Cristiane; Colet, Christiane de Fátima; Benetti, Eliane Rieth; Kleibert, Karine Raquel Uhdich; Vaz, Simone Minuzzi Catto; Treviso, Patricia; Stumm, Eniva Miladi (O Mundo da Saúde, 2023)
Musculoskeletal pain is a frequent problem in nursing professionals, and several treatments have been researched to reduce it; however, few studies address the influence of increased resilience of these professionals in controlling their pain. Thus, this study aimed to identify an association between resilience and musculoskeletal pain reported by nursing professionals in different anatomical regions. This is a cross-sectional observational study with 321 nursing professionals. A sociodemographic and work questionnaire, a Nordic musculoskeletal symptoms questionnaire, an analog pain scale, and a resilience scale were used. Descriptive and analytical statistics were used for analysis, using the Mann-Whitney U and Kruskal Wallis tests. The relationships between pain and sociodemographic, work, and resilience characteristics were analyzed. 261 (81.3%) reported having had musculoskeletal pain in the last year, and the most affected regions were the upper and lower backs and shoulders. An association was identified between pain intensity and musculoskeletal pain in all investigated body regions (p < 0.05), age (p = 0.015), professional category (p = 0.032), length of experience in nursing (p = 0.003), and work shift (p = 0.012). A correlation was also observed between resilience and musculoskeletal pain in the neck (p = 0.010) and hip and thighs (p = 0.009). Thus, high resilience is associated with better control of musculoskeletal pain among nurses, especially in the neck region.